Logistic Activity of The Trade Enterprise: Essential Charachteristics and Formalization of Model - T. Shtal; A. Uvarova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article explores the scientific views on the content of the logistics activities of the enterprise. The essential characteristics of the logistics activities are provided taking into account the functional and process approaches, taking into account the functional, operational and managerial aspects of the processes and operations. The definitions of the concept of the logistics activities of the enterprise are given in compliance with the process-functional approach. The features of logistic flows of a trade enterprise are investigated. Taking into account the main functions of the trade enterprise and the tasks of logistics, a model of the enterprise's logistics activities has been built and justified.